Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fphar.2019.00999
|View full text |Cite
|
Sign up to set email alerts
|

Neferine Promotes GLUT4 Expression and Fusion With the Plasma Membrane to Induce Glucose Uptake in L6 Cells

Abstract: Glucose transporter 4 (GLUT4) is involved in regulating glucose uptake in striated muscle, liver, and adipose tissue. Neferine is a dibenzyl isoquinoline alkaloid derived from dietary lotus seeds and has multiple pharmacological effects. Therefore, this study investigated neferine’s role in glucose translocation to cell surface, glucose uptake, and GLUT4 expression. In our study, neferine upregulated GLUT4 expression, induced GLUT4 plasma membrane fusion, increased intracellular Ca2+, promoted glucose uptake, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…IRS1 and PI3 K mRNA levels were also increased by the action of insulin and bark extract. The same conclusion was reached by Zhao et al (2019) who reported an increase mRNA expression level of GLUT-4, following a treatment of L6 with neferine, an alkaloid derived from lotus seeds and insulin. 46 There was an upregulation of Akt1, Akt2 and peroxisome proliferator-activated receptor g (PPAR-g) in C2C12 cells treated with leaf and seed extracts (Figure 4).…”
Section: Gene Expression Of Irs1 Pi3 K Akt1 Akt2 Ppar-g and Glut-4supporting
confidence: 70%
“…IRS1 and PI3 K mRNA levels were also increased by the action of insulin and bark extract. The same conclusion was reached by Zhao et al (2019) who reported an increase mRNA expression level of GLUT-4, following a treatment of L6 with neferine, an alkaloid derived from lotus seeds and insulin. 46 There was an upregulation of Akt1, Akt2 and peroxisome proliferator-activated receptor g (PPAR-g) in C2C12 cells treated with leaf and seed extracts (Figure 4).…”
Section: Gene Expression Of Irs1 Pi3 K Akt1 Akt2 Ppar-g and Glut-4supporting
confidence: 70%
“…Second, Ca 2+ signaling affects glucose utilization by regulating the insulin signaling pathway. The G protein/IP3/IP3R pathway is involved in glucose transporter 4 (GLUT4)-plasma membrane fusion, while pharmaceutically induced GLUT4-plasma membrane fusion and glucose uptake are inhibited by treatment with a Ca 2+ chelator, suggesting that these processes are Ca 2+dependent (35).…”
Section: Calcium Homeostasismentioning
confidence: 99%
“…GLUT4 is an insulin-responsive glucose transporter that mediates glucose influx in the muscle cells. It has been reported that GLUT4 expression and translocation could be regulated through the G-protein-phospholipase C-protein kinase C and 5' adenosine monophosphate (AMP)-activated protein kinase pathway in muscle cells (37). Impaired expression of GLUT4 has been reported to be linked to obesity, type 1 diabetes, and type 2 diabetes (38).…”
Section: Discussionmentioning
confidence: 99%